Determining the Effect of an Innovative Biofeedback SKOL-AS® Treatment on the Body Posture and Trunk Rotation in Children with Low Grade Idiopathic Scoliosis - Anna M. Kamelska-Sadowska; Halina Protasiewicz-Faldowska; Lidia Zakrzewska; Katarzyna Zaborowska-Sapeta; Jacek J. Nowakowski; Ireneusz M. Kowalski (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
The deformity in idiopathic scoliosis (IS) is three dimensional and effective correction should involve all three planes. Recently, the biofeedback method has been implemented in the treatment of scoliosis. The aim of this study was to evaluate the effectiveness of an innovative biofeedback SKOL-AS® postural training among children with scoliosis. The target population for this study was 28 patients (25 girls and 3 boys) aged between 5 and 16 years old diagnosed and treated with low-grade progressing scoliosis. The postural diagnosis consisted of anthropometric measurements, posterior–anterior X-ray imaging, SpinalMeter® postural assessment and the angle of trunk rotation (ATR) assessment. The SKOL-AS® treatment comprised of 24 sessions conducted in lying and sitting positions, two times a week for three months. The study indicated that the postural training resulted in the decrease in the ATR value (pre- vs. post-exercise in younger: 5.5\(^°\) vs. 3.0\(^°\) and older patients: 5.2\(^°\) vs. 3.0\(^°\)). The increase in height of the subjects seemed to confirm a positive elongation effect of SKOL-AS® treatment. In the posterior view, a statistically significant decrease in shoulder asymmetry in the sitting position in younger children has been observed. In the anterior view, the changes in the head position (based on mouth and eye symmetry) have been observed. The statistically significant increase in acromion–heel, acromion–iliac crest and posterior superior iliac spine (PSIS)–heel length values has been shown in younger children on the left side of the body. After treatment, older subjects had higher acromion–iliac crest and PSIS–heel values on the left side of the body. On the right side only PSIS–heel length was higher. In a sitting position, only a small increase in acromion–iliac crest length value has been observed. This study has established that the SKOL-AS® biofeedback method could teach good postural habits and teach patients the auto-correction of the spine in all three planes.